Pengaruh Ukuran Perusahaan,Laba Rugi Perusahaan, Profitabilitas, Solvabilitas, Opini Auditor Dan Ukuran KAP Terhadap Audit Delay (Studi Pada Perusahaan Sektor Keuangan Yang Terdaftar Di BEI Periode 2011-2014) - Wulandari, Diah Ayu, Fauzan, S.E., M.Si., Ak (2017)
The purpose of this research is to examine the signification impact of company size, profit loss company, profitability, solvability, auditor opinion and size of a public accountant toward audit delay. The population of this research is financial sector companies listed in Indonesia Stock Exchange during 2011-2014. Sampling technique that used in this study is the purposives sampling. The method of analysis used to the test the hypothesis is multiple linear regression analysis. The sample used in this study are 57 companies. The Result ofthis research show that company size, profitability, solvability, auditor opinion and size of a public accountant have significant effect on audit delay, while profit loss company have no significant effect on audit delay. Keywords : Audit Delay, Company Size, Profit Loss Company, Profitability, Solvability, Auditor's Opinion And Size Of A Public Accountant